(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Currently, there is an unsolved problem of IoT device authentication in networks to ensure their security. Due to low performance, work with traditional methods of protection is complicated and therefore a different approach is required. The article proposes a method for authenticating IoT devices (devices and software) by verifying their data and then entering it into the data storage. The implementation of a data storage using blockchain technology and the comparison of its efficiency with a classical database are considered. The aim of research is evelopment of the IoT device authentication method, analysis of the effectiveness and applicability of the developed method and comparison of various technological approaches to solving the problem. Obtained results is evaluation parameters of the resulting system and methods for constructing systems based on this method.